Metagenomic and Resistome Analysis of a Full-Scale Municipal Wastewater Treatment Plant in Singapore Containing Membrane Bioreactors - Ng, Charmaine; Tan, Boonfei; Jiang, Xiao-Tao; Gu, Xiaoqiong; Chen, Hongjie; Schmitz, Bradley William; Haller, Laurence; Charles, Francis Rathinam; Zhang, Tong; Gin, Karina (Frontiers in Microbiology, 2019)
Reclaimed water provides an alternative source of water supply to address problems of water scarcity in urbanized cities with high living densities and limited natural water resources. In this study, wastewater metagenomes from 6 stages of a wastewater treatment plant (WWTP) integrating conventional and membrane bioreactor (MBR) treatment were evaluated for diversity of antibiotic resistance genes (ARGs) and bacteria, and relative abundance of class 1 integron integrases (intl1). ARGs confering resistance to 12 classes of antibiotics (ARG types) persisted through the treatment stages, which included genes that confer resistance to aminoglycoside (aadA, aph(6)-I, aph(3’)-I, aac(6’)-I, aac(6’)-II, ant(2”)-I), beta-lactams [class A, class C, class D beta-lactamases (blaOXA)], chloramphenicol (acetyltransferase, exporters, floR, cmIA), fosmidomycin (rosAB), macrolide-lincosamide-streptogramin (macAB, ereA, ermFB), multidrug resistance (subunits of transporters), polymyxin (arnA), quinolone (qnrS), rifamycin (arr), sulfonamide (sul1, sul2) and tetracycline (tetM, tetG, tetE, tet36, tet39, tetR, tet43, tetQ, tetX). Although the ARG subtypes in sludge and MBR effluents reduced in diversity relative to the influent, clinically relevant beta lactamases (i.e. blaKPC, blaOXA) were detected, casting light on other potential point sources of ARG dissemination within the wastewater treatment process. To gain a deeper insight into the types of bacteria that may survive the MBR removal process, genome bins were recovered from metagenomic data of MBR effluents. A total of 101 close to complete draft genomes were assembled and annotated to reveal a variety of bacteria bearing metal resistance genes and ARGs in the MBR effluent. Three bins in particular were affiliated to Mycobacterium smegmatis, Acinetobacter Iwoffii, and Flavobacterium psychrophila, and carried aquired ARGs aac(2’)-Ib, blaOXA-278, and tet36 respectively. In terms of indicator organisms, cumulative log removal values (LRV) of Escherichia coli, Enterococci, and P. aeruginosa from influent to conventional treated effluent was lower (0-2.4), compared to MBR effluent (5.3-7.4). We conclude that MBR is an effective treatment method for reducing fecal indicators and ARGs; however, incomplete removal of P. aeruginosa in MBR treated effluents (<8 MPN/100 mL) and the presence of ARGs and intl1 underscores the need to establish if further treatment should be applied prior to reuse.